Research on the mechanical properties prediction of carbon/epoxy composite laminates with different void contents. Issue 1 (28th July 2014) - Zhang, Aying; Lu, Haibao; Zhang, Dongxing
Abstract : The influence of the porosity on the static mechanical strength of the carbon fiber fabric reinforced epoxy composites laminates was investigated. The tensile, compressive, bending, and interlaminar strength test on the CFRP laminates with porosity of 0.33% and 1.50% were conducted and simulated by a finite element analysis model. The article proposes the failure criterion of the static mechanical strength of the fabric fiber reinforced composites based on the improved Hashin failure criterion that is suitable for the undirectional composite laminates. The basic composite strength parameters are used to evaluate the mechanical properties of CFRP laminates with different porosities. A finite element analysis model is established by using software ABAQUS™ combined with the sudden stiffness degradation model. The experiment results show that the tensile, compressive, bending, and interlaminar strength decrease with the increasing porosities. The tensile, compressive, bending, and interlaminar strength of the fabric carbon fiber reinforced epoxy composites laminates are simulated accurately by the finite element model. POLYM. COMPOS., 14–20, 2016. © 2014 Society of Plastics Engineers